Analisis Pembentukan Portofolio Saham Optimal menggunakan Pendekatan Model Indeks Tunggal sebagai Dasar Keputusan Investasi : Studi pada Saham-Saham IDXV30 yang Listing di Bursa Efek Indonesia (BEI) Tahun 2022-2024 (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the formation of an optimal stock portfolio using the Single Index Model on IDX Value30 stocks listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. A quantitative method was applied using secondary data from 17 selected stocks. Only five stocks (ADRO, ASII, MNCN, PTBA, and TKIM) were included in the optimal portfolio based on Excess Return to Beta (ERB) values above the Cut-off Point (C*). The resulting portfolio offers an expected return of 2.70% with minimal systematic risk and 0.74% unsystematic risk. These findings demonstrate the effectiveness of the Single Index Model in constructing an efficient portfolio and supporting investment decision-making in the Indonesian capital market.